Розробка інформаційної системи обліку вантажоперевезень - Калюжний, О. Д. (ХНУРЕ, 2024)
The work considers the relevance of developing an information system for optimizing cargo accounting. Analysis of trends in the field of freight transportation serves to introduce innovative functions. The assessment of system efficiency takes into account the speed and convenience of data processing in the freight transportation system.
Keywords: облік вантажоперевезень; інформаційна система; управління вантажами; трекінг перевезень; логістичний облік